Consequences of natal philopatry for reproductive success and mate choice in an Alpine rodent. (15th March 2016) - García-Navas, Vicente; Bonnet, Timothée; Waldvogel, Dominique; Camenisch, Glauco; Postma, Erik
Lay Summary: Group living in snow voles does not constitute an adaptive strategy, rather it seems to be the best of a bad job. Individuals may tolerate inbreeding as the costs of developing inbreeding avoidance may be high due to limited natal dispersal. In addition, the existence of postmating mechanisms may impede strong selection for premating inbreeding avoidance. Thus, opposite premating and postmating strategies can coexist within the same population. Abstract: Quantifying the interaction between dispersal, kinship, and genetic structure can provide insights into the factors that shape kin-structured mammal societies. Here, we first employ a combination of 8 years of capture–mark–recapture and molecular data to characterize the spatial and genetic relationships among female snow voles ( Chionomys nivalis ) in a population located in the Swiss Alps. Subsequently, we examine the individual-level consequences of kin structure in terms of fitness and mating patterns. Behavioral data, relatedness estimates, and spatial autocorrelation analyses indicate that females show strong philopatry, with spatially clustered females being characterized by high levels of genetic relatedness, leading to significant small-scale (<30 m) spatial genetic structure (SGS). In line with selection favoring female philopatry, dispersing females had a lower fitness compared with philopatric individuals. However, we found a negative association between female reproductive success and the number of neighboring females. This suggests that female kin clustering does not constitute an adaptive strategy in this species, but rather that site tenacity is a by-product of the costs of dispersal. Although dispersal is frequently invoked as a means to avoid inbreeding, our results provide no evidence for premating inbreeding avoidance, which is in line with previous studies on mammals. Instead, in the majority of years, we observed that pairs were more-closely related than expected by chance. However, we found that both males and females with related partners had reduced reproductive success, suggesting the existence of inbreeding depression and/or postmating inbreeding avoidance mechanisms. On the whole, our results show how quantification of SGS within populations can provide insights into individual dispersal behavior and its fitness consequences, and into the ways in which social and genetic structure interacts to shape the evolution of free-living populations.